2015
DOI: 10.1371/journal.pone.0125331
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin Is Involved in Patients with IgG4 Related Disease

Abstract: ObjectiveIgG4-related disease (IgG4-RD) is a chronic systemic disease involved in many organs and tissues. As only limited autoantigens have been found since the beginning of this century, the aim of this study was to reveal new candidate autoantigens of IgG4-RD.MethodsMultiple cell lines including HT-29, EA.hy926, HEK 293 and HepG2 were used to test the binding ability of circulating autoantibodies from IgG4-RD sera. The amino-acid sequence was then analyzed by matrix-assisted laser desorption/ionization time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 32 publications
(31 reference statements)
1
56
2
3
Order By: Relevance
“…Anti–laminin 511‐E8 IgG was detected in only 1% of our IgG4‐RD cohort, which is comparable to the 1.6% response frequency observed among controls by Shiokawa et al, but markedly below the 51% frequency reported in their cohort of IgG4‐related AIP patients . Similarly, although anti‐prohibitin IgG4 was reported to occur in 73% of IgG4‐RD patients with diverse organ manifestations , we found only 10% IgG4 reactivity among the patients in our similarly diverse cohort. One possible explanation for these discrepancies may be related to genetic differences between the studied cohorts.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Anti–laminin 511‐E8 IgG was detected in only 1% of our IgG4‐RD cohort, which is comparable to the 1.6% response frequency observed among controls by Shiokawa et al, but markedly below the 51% frequency reported in their cohort of IgG4‐related AIP patients . Similarly, although anti‐prohibitin IgG4 was reported to occur in 73% of IgG4‐RD patients with diverse organ manifestations , we found only 10% IgG4 reactivity among the patients in our similarly diverse cohort. One possible explanation for these discrepancies may be related to genetic differences between the studied cohorts.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast to annexin A11 and laminin 511‐E8, only anti‐prohibitin antibodies had been reported in the context of multiorgan systemic IgG4‐RD , thereby permitting a direct comparison to the present cohort. The frequency of anti‐prohibitin responses observed among the systemic and clinically diverse cohort was 10%.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…One important difference between that study and ours is that we included patients with diverse manifestations of IgG4-RD; in fact, only 19% of the patients in our cohort have had pancreatic involvement, and only 3 of the patients who had a history of malignancy had IgG4-related AIP. The pathogenesis of IgG4-RD remains poorly understood, but it is generally recognized as an immunemediated condition (9) which may be mediated by autoimmunity (18,19), Th2-polarized and T regulatory lymphocytes (20), and/or oligoclonally expanded circulating plasmablasts (8,21). Associations between allergic conditions and IgG4-RD may suggest a shared pathogenesis between the 2 conditions (22).…”
Section: Discussionmentioning
confidence: 99%
“…(18) In another study, Prohibitin (PHB), a gene associated with various functions including mitochondrial function and transcriptional modulation, was identified as a possible auto-antigen. (19)…”
Section: Autoimmune Pancreatitismentioning
confidence: 99%